2015
DOI: 10.5194/acpd-15-31705-2015
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Anvil microphysical signatures associated with lightning-produced NO<sub><i>x</i></sub>

Abstract: Abstract. Thunderstorm anvils were studied during the Deep Convective Clouds and Chemistry experiment (DC3), using in situ measurements and observations of ice particles and NOx together with radar and lightning mapping array measurements. A characteristic ice particle and NOx signature was found in the anvils from three storms, each containing high lightning flash rates in the storm core prior to anvil sampling. This signature exhibits high concentrations of frozen droplets (as measured by a Cloud Droplet Pro… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…The laboratory studies of Saunders and Wahab () and Wahab () showed that in a vertical electric field (i.e., the field was aligned with the direction of fall) a threshold of ice crystal concentration of 250/L and an electric field threshold of ~60 kV/m was required in order to enhance aggregation. In another study Stith et al () have observed chain‐like aggregation of frozen cloud droplets in the upper parts of some anvils in association with high values of NO x in which lightning was known to have occurred. They attributed the aggregation of frozen droplets to electric field forces.…”
Section: Observations Of Microphysical Content In Deep Stratiform Cloudsmentioning
confidence: 95%
“…The laboratory studies of Saunders and Wahab () and Wahab () showed that in a vertical electric field (i.e., the field was aligned with the direction of fall) a threshold of ice crystal concentration of 250/L and an electric field threshold of ~60 kV/m was required in order to enhance aggregation. In another study Stith et al () have observed chain‐like aggregation of frozen cloud droplets in the upper parts of some anvils in association with high values of NO x in which lightning was known to have occurred. They attributed the aggregation of frozen droplets to electric field forces.…”
Section: Observations Of Microphysical Content In Deep Stratiform Cloudsmentioning
confidence: 95%
“…On the other hand, small cloud droplets are often transported up to the homogeneous freezing level in strong updrafts formed in midlatitude continental convection (Lawson et al, ; Rosenfeld & Woodley, ). The high concentrations of small droplets in the updrafts either can participate in riming or, after homogeneous freezing, can form aggregates (e.g., Stith et al, , ). Anvils generally form at temperatures colder than −38 °C, so all supercooled liquid water is frozen and the ice rapidly depletes the supersaturated fraction of water vapor in the anvil, driving RH ice down to 100% (Diao et al, ; Jensen et al, ), which inhibits formation and growth of polycrystals and rosettes (Bailey & Hallett, ).…”
Section: Overview Of Particle Shapes In Anvil and In Situ Cirrusmentioning
confidence: 99%
“…Analyses of cloud physical properties were conducted using aircraft measurements of cloud particle size distributions (Stith et al, ) and water vapor (Diao et al, ), as well as balloon‐borne video disdrometer (Waugh et al, ). The recently developed balloon‐borne microphysics probe can provide observations at fine scales and give calculated cloud particle mixing ratios and reflectivity in agreement with radar and cloud‐resolving, kinematic model results.…”
Section: Findings From Dc3mentioning
confidence: 99%
“…The frozen drop aggregates are formed by electrical forces associated with high electric fields accompanying lightning. Since lightning is also the source of lightning‐NO x , these studies suggested that electrically active storms may have characteristically different ice particle types in the anvil compared to less electrically active storms, which may have an impact on the radiative impacts of the anvil clouds (Stith et al, ).…”
Section: Findings From Dc3mentioning
confidence: 99%